2009
DOI: 10.3171/2008.11.jns08858
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance imaging for preoperative identification of the lenticulostriate arteries in insular glioma surgery

Abstract: Aggressive resection of insular tumors is possible using a meticulous surgical approach based on the regional insular anatomy, with high rates of gross-total resection and low rates of permanent neurological deficits. However, the risk of postoperative morbidities remains high, often caused by disruption of the vascular supply to the surrounding eloquent structures, especially the lenticulostriate arteries (LSAs) that supply the internal capsule. Three-dimensional 3-T time-of-flight (TOF) MR imaging was perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0
7

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 14 publications
1
30
0
7
Order By: Relevance
“…In insular gliomas surgery, an injury to the lateral lenticulostriate arteries represents the main cause of permanent neurological deficit, leading to permanent hemiparesis due to a deep stroke in the internal capsule. 8,19,28,31 The present work revealed that in insulo-opercular gliomas, the distance between the limen insulae and the IFOF and uncinate fasciculus was enlarged, while the distance between the lateral margin of the anterior perforated substance and the lateral surface of the tracts was reduced. Consequently, at the limen insulae, gliomas seem to grow in the space between the tracts and the insular surface, compressing the tracts in a medial direction.…”
Section: Transopercular Approach To Insulo-opercular Gliomassupporting
confidence: 47%
“…In insular gliomas surgery, an injury to the lateral lenticulostriate arteries represents the main cause of permanent neurological deficit, leading to permanent hemiparesis due to a deep stroke in the internal capsule. 8,19,28,31 The present work revealed that in insulo-opercular gliomas, the distance between the limen insulae and the IFOF and uncinate fasciculus was enlarged, while the distance between the lateral margin of the anterior perforated substance and the lateral surface of the tracts was reduced. Consequently, at the limen insulae, gliomas seem to grow in the space between the tracts and the insular surface, compressing the tracts in a medial direction.…”
Section: Transopercular Approach To Insulo-opercular Gliomassupporting
confidence: 47%
“…This "windowing technique" permits tumor removal along the course of the uncinate fasciculus, generating supra-and infrasylvian resection cavities that are eventually connected to one another underneath the skeletonized sylvian vessels. Finally, identification of the lenticulostriate arteries 10 and motor mapping of the internal capsule allows delineation of the medial border of resection in most cases. …”
Section: Microsurgical Techniquementioning
confidence: 99%
“…Согласно R. Saito и соавт. [17], визу-ализация ЛСА в предоперационном периоде с по-мощью 3D-TOF МРА позволяет снизить риск их интраоперационного повреждения и увеличить сте-пень резекции опухоли. Однако авторы не указыва-ют числа пациентов, которым сделано исследова-ние, а приводят лишь три клинических примера ис-пользования методики.…”
Section: рис 4 клиническое наблюдение 4 повреждение дистального учunclassified